MEDICAL AND PEDAGOGICAL SUPPORT OF REMOTE LESSONS FOR STUDENTS WITH DISABILITIES - Светлана Николаевна Викжанович; Ольга Юрьевна Синевич; Татьяна Юрьевна Четверикова (The Publishing House Medicine and Enlightenment, 2021)
The authors address the issues of medico-pedagogical navigation of education and rehabilitation online process involving school students with disabilities. The article examines how distance learning practices can be supported during the pandemic's restrictive measures. Recommendations are made on how to organize a virtual school architecture that meets children's health and safety requirements. The content that can be used in virtual classrooms and rooms to provide remedial classes, rehabilitation activities, support leisure activities and education for school students with developmental disabilities, as well as psychological and pedagogical support for parents and methodological assistance for specialists is described.